Variation of Nonlinear Refraction and Three-Photon Absorption of Indium–Tin Oxide Quantum Dot Thin Films and Solutions in Near Infrared Range - Bundulis, Arturs; Berzina, Anete; Kim, Vyacheslav V.; Polyakov, Boris; Novikovs, Aleksandrs; Ganeev, Rashid A. (MDPI, 2023)
We characterize the nonlinear optical properties of indium–tin oxide (ITO) quantum dots (QDs) in the IR range using the Z-scan method. We present results of three-photon absorption (3PA), third harmonic generation (3HG), and Kerr-effect-induced nonlinear refraction in ITO QDs. Z-scan measurements were carried out for the QDs solution, while 3HG was demonstrated using QD thin films. The Kerr-induced nonlinear refractive index was analyzed along the 800–950 nm range showing an increase in this parameter from −6.7 × 10−18 to −1.5 × 10−17 m2 W−1. At longer wavelengths (1000–1100 nm), the higher-order effects started to contribute to a nonlinear refractive index. The 3PA coefficient at 950 nm was measured to be 1.42 × 10−25 m3/W2. We discuss the peculiarities in the wavelength-dependent variation of the coefficient of nonlinear absorption responsible for 3PA in the range of 800–1150 nm. Third harmonic generation was analyzed in the 1200–1550 nm spectral range. The absolute value of 3HG conversion efficiency in the 150 nm thick film at the wavelength of laser radiation (1350 nm) was estimated to be ~10–5. --//-- This is an open access article Bundulis, A.; Berzina, A.; Kim, V.V.; Polyakov, B.; Novikovs, A.; Ganeev, R.A. Variation of Nonlinear Refraction and Three-Photon Absorption of Indium–Tin Oxide Quantum Dot Thin Films and Solutions in Near Infrared Range. Nanomaterials 2023, 13, 2320. https://doi.org/10.3390/nano13162320 published under the CC BY 4.0 licence.
Authors acknowledge the support of J. Grube and A. Sarakovskis in providing the laser facility for these studies. Institute of Solid State Physics, University of Latvia as the Center of Excellence has received funding from the European Union’s Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; indium–tin oxide; quantum dots; Kerr effect; three-photon absorption; third harmonic generation